Dihydrofolate reductase-like protein inactivates hemiaminal pharmacophore for self-resistance in safracin biosynthesis - Ning Shao; Xueyang Ma; Ying-Ying Zhang; Donghui Yang; Ming Ma; Gong-Li Tang (Elsevier, 2023)
Dihydrofolate reductase (DHFR), a housekeeping enzyme in primary metabolism, has been extensively studied as a model of acid-base catalysis and a clinic drug target. Herein, we investigated the enzymology of a DHFR-like protein SacH in safracin (SAC) biosynthesis, which reductively inactivates hemiaminal pharmacophore-containing biosynthetic intermediates and antibiotics for self-resistance. Furthermore, based on the crystal structure of SacH−NADPH−SAC-A ternary complexes and mutagenesis, we proposed a catalytic mechanism that is distinct from the previously characterized short-chain dehydrogenases/reductases-mediated inactivation of hemiaminal pharmacophore. These findings expand the functions of DHFR family proteins, reveal that the common reaction can be catalyzed by distinct family of enzymes, and imply the possibility for the discovery of novel antibiotics with hemiaminal pharmacophore.